Peran Program Kampus Mengajar dalam Meningkatkan Kompetensi Keguruan pada Mahasiswa Program Studi Pendidikan Agama Islam - Arifah, Mir'atun Nur; Wahyuningsih, Wahyuningsih (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
One part of the MBKM program is Kampus Mengajar, which provides students with experience to assist teachers in the learning process in the classroom. This qualitative research investigates the role of Kampus Mengajar in improving the teaching abilities of students in the Islamic Education Study Program. After research data was collected through observation, interviews and documentation techniques, triangulation techniques were used to ensure its validity. There are three stages of analysis used: reducing data, displaying data, and drawing conclusions. The research results show Kampus Mengajar helps improve the teaching competence of students in the Islamic Education Study Program. Students gain pedagogical, professional, personality and social competence through the various activities they carry out. During Kampus Mengajar, students can acquire these competencies through the various activities they participate in. With a wider choice of activities compared to other practical programs, such as PPL and internships, Kampus Mengajar has the ability to complement students' experiences by being directly involved in the educational process in Indonesia.